The coming of age of East Asian cosmopolitan nation-state universities in the SDGs era: at the crossroads of internationalization, global governance, and nation-statehood - Sarah R. Asada; Kazuo Kuroda (Journal of Contemporary East Asia Studies, 2024)
The purpose of this special issue dedicated to the current realities of East Asian global universities is to consider the future of the internationalization higher education in the region and beyond as the world grapples with the precarious balancing act of international cooperation and national competition. Collectively, the eight articles paint a picture of a region undergoing redefinition of their ideals and objectives for institutional internationalization and transforming their mission in alignment with emerging global governance frameworks, with a focus on the Sustainable Development Goals (SDGs). To understand the nature of global universities in East Asia, it is important to review the changes in the international dimension of higher education and how global governance and nation-statehood contributes to their mission. Given the prominent role higher education play in national development in a globalized world, this special issue is at the heart of the coming of age of the East Asian Cosmopolitan Nation-State University, grounded in the theoretical and contextual foundations of internationalization, providing a review of its theoretical and contextual foundations centered upon institutional transformation through internationalization, global governance, and nation-statehood.